THE EFFECT OF CUSTOMER SATISFACTION, CUSTOMER RETENTION, AND ITS IMPACT ON THE TOURISM SECTOR IN LAMPUNG BEACH - Sari, Dewi Komala; Barusman, Andala Rama Putra (jfpublisher, 2025)
By studying beach tourism in South Lampung, Indonesia, researchers assess how customer satisfaction affects customer retention. In this study use variables, service quality, promotion, and destination image, with using the mediating variable and customer satisfaction and the endogenous variable customer retention, this article employs the Structural Equation Model (SEM) technique with 360 respondents, revealing a relationship where customer retention is influenced by service quality, promotion, destination image variables mediated by customer satisfaction. Therefore, researchers recommend several strategies for the Lampung Provincial government, namely being able to enhance promotions, providing good service to improve service quality, and developing adequate facilities that can be utilized by visitors to enhance destination image variables.